(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Determine species composition, distribution, biting habits and medical role of blackflies in Sin Thau and Sen Thuong communes, Muong Nhe district, Dien Bien province. Research method: Time of implementation from August to December 2024. Collect adult blackflies by using nets and livestock bait. Immature stages are collected through substrates. Dissect to find parasites according to WHO 2002 procedures. Assess the damage to people when bitten by blackflies through direct interviews. Results: 462 blackflies of 20 species were collected at the survey points. In Sin Thau commune, there were 19 species, Sen Thuong commune, 11 species. Three species were recorded to suck buffalo blood: Simulium nigrogilvum, Simulium striatum, Simulium asakoae. In particular, S. nigrogilvum also sucks human blood. Blackflies bite from 7 am to 5 pm, most strongly from 7 am to 10 am and from 4 pm to 5 pm. Interviews with 400 people showed that blackflies bit 100%. Common lesions when bitten by blackflies include bleeding, burning, and itching, accounting for 100%. Dissection of 223 individuals belonging to 3 species, S. nigrogilvum, S. striatum, and S. asakoae, only found parasites in Simulium nigrogilvum. Conclusion: 462 adult blackflies were collected, belonging to 20 species, 3 subgenera, and 1 genus of the family Simulidae. The 3 species S. nigrogilvum, S. striatum, S. asakoae were recorded to suck blood from humans and buffalo. The rate of substrate infected with fruit fly larvae and pupae was 83.26%. Burning bait is from 7 am to 5 pm, peaking from 8 am to 9 am. People bitten by blackflies all have some common initial injuries: there are symptoms of bright red blood clots, itching, and a burning sensation with a red rash around the bite. S. nigrogilvum species is infected with parasites in the abdomen and thorax, with an infection rate of 2%.